Punjab State Board PSEB 6th Class Maths Book Solutions Chapter 4 Integers Ex 4.2 Textbook Exercise Questions and Answers.

## PSEB Solutions for Class 6 Maths Chapter 4 Integers Ex 4.2

1. Using number line write the integer which is:

Question (a)

5 less than -1

Solution:

5 less than -1 = ?

We need to find the integer which is 5 less than -1.

So, we shall start with ‘-1 ’ and proceed 5 steps to the left of -1 as shown below:

Therefore 5 less than -1 is -6

Question (b)

5 more than -5

Solution:

5 more than -5 = ?

We need to find the integer which is 5 more than -5.

So, we shall start with -5 and proceed 5 steps to the right of -5 as shown below:

Therefore 5 more than -5 is zero.

Question (c)

2 less than 5

Solution:

2 less than 5 = ?

We need to find the integer which is 2 less than 5.

So, we shall start with 5 and proceed

2 steps to the left of 5 as shown below:

Therefore 2 less than 5 is 3.

Question (d)

3 less than -2.

Solution:

3 less than – 2 = ?

We need to find the integer which is 3 less than -2.

So, we shall start with -2 and proceed 3 steps to the left of -2 as shown below:

Therefore 3 less than -2 is -5.

2. Using number line, add the following integers:

Question (a)

9 + (-3)

Solution:

On number line we shall start from 0 and move 9 steps to the right of zero. Then we shall move three steps to the left of ‘+9’. We finally reach at +6. Thus, +6 is the answer.

Hence, 9 + (-3) = +6

Question (b)

5 + (-11)

Solution:

On number line we shall start from 0 and move 5 steps to the right of zero. Then we shall move eleven steps to the left of ‘+5’. We finally reach at ‘-6’. Thus, -6 is the answer.

Hence, 5 + (-11) = -6

Question (c)

(-1) + (-4)

Solution:

On number line we first move 1 step to the left of zero. Then we moved ahead 4 steps to the left of ‘-1\ We finally reaches at -5. Thus -5 is the answer.

Hence, (-1) + (-4) = -5

Question (d)

(-5) + 12

Solution:

On number line we shall move 5 steps to the left of zero. Then we shall move 12 steps to the right of ‘-5’ and finally reach at ‘+7’. Thus +7 is the answer.

Hence, (-5) + 12 = +7

Question (e)

(-1) + (-2) + (-4)

Solution:

Step I: On number line we shall move one step to the left of zero suggested by minus sign of ‘-1’.

Step II: Then we shall move 2 steps to the left of -1 suggested by minus sign of -2 and we reach at ‘-3’.

Step III: Then again we shall move 4 steps to the left of ‘-3’ suggested by minus sign of -4 and finally we reach at-7.

Hence, (-1) + (-2) + (-4) = -7

Question (f)

(-2) + 4 + (-5)

Solution:

Step I: On number line we shall move 2 steps to the left of zero suggested by minus sign of ‘-2’.

Step II: Then we shall move 4 steps to the right of ‘-2’ suggested by plus sign of ‘44’ and we reach at +2.

Step III: Then we shall move 5 steps to the left of ‘+2’ as suggested by minus sign of ‘-5’ and finally we reach at -3. Thus answer is ‘-3’.

Hence, (-2) + 4 + (-5) = -3

Question (g)

(-3) + (5) + (-4).

Solution:

Step I: On number line we shall move 3 steps to the left of zero as suggested by minus sign of ‘-3’.

Step II: Then we shall move 5 steps to the right of ‘-3’ as suggested by plus sign of ‘+5’ and we reach at ‘+2’.

Step III: Then we shall move 4 steps to the left of ‘+2’ as suggested by minus sign of ‘4’ and finally we reach at ‘-2’. Thus ‘-2’ is the answer.

Hence, (-3) + (5) + (-4) = -2

3. Add without using number line:

Question (a)

18 + 13

Solution:

18 + 13 = 31

Question (b)

18 + (- 13)

Solution:

18 + (- 13) = + (18 – 13) = +5

Question (c)

(-18) + 13

Solution:

(-18) + 13 = – (18 – 13) = -5

Question (d)

(-18) + (-13)

Solution:

(-18) + (-13) = -(18 + 13) = -31

Question (e)

180 + (-200)

Solution:

180 + (-200) = -(200 – 180) = -20

Question (f)

111 + (-67)

Solution:

111 + (-67) = (777 – 67) = 710

Question (g)

1262 + (-366) + (-962)

Solution:

1262 + (-366) + (-962)

= 1262 – (366 + 962)

= 1262 – 1328

= -(1328 – 1262) = -66

Question (h)

30 + (-27) + 21 + (-19) + (-3) + 11 + (-9)

Solution:

30 + (-27) + 21 + (-19) + (-3) + 11 + (-9)

= 30 + 21 + 11 + (-27) + (-19) + (-3) + (-9)

= 62 + (-58) = 62 – 58 = 4

Question (i)

(-7) + (-9) + 4 + 16

Solution:

(-7) + (-9) + 4+16 = (-16) + 20 = 4

Question (j)

37 + (-2) + (-65) + (-8).

Solution:

37 + (-2) + (-65) + (-8)

= 37 – (2 + 65 + 8)

= 37 – 75 = -38

4. Write the successor and predecessor of the following:

Question (a)

-15

Solution:

Successor of -15 = -15 + 1 = -14

Predecessor of -15 = -15 – 1 = -16

Question (b)

27

Solution:

Successor of 27 = 27 + 1 = 28

Predecessor of 27 = 27 – 1 = 26

Question (c)

-79

Solution:

Successor of -79 = -79 + 1 = -78

Predecessor of -79 = -79- 1 = -80

Question (d)

0

Solution:

Successor of 0 = 0+ 1 = 1

Predecessor of 0 = 0 – 1 = -1

Question (e)

29

Solution:

Successor of 29 = 29 + 1 = 30

Predecessor of 29 = 29 – 1 = 28

Question (f)

-18

Solution:

Successor of -18 = -18 + 1 = -17

Predecessor of -18 = -18 – 1 = -19

Question (g)

-21

Solution:

Successor of -21 = -21 + 1 = -200

Predecessor of -21 = -21 – 1 = -22

Question (h)

99

Solution:

Successor of 99 = 99 + 1 = 100

Predecessor of 99 = 99 – 1 = 98

Question (i)

-1

Solution:

Successor of-1 = -1 + 1 = 0

Predecessor of -1 = -1 – 1 = -2

Question (j)

-13.

Solution:

Successor of -13 = -13 + 1 = -12

Predecessor of -13 = -13 – 1 = -14

5. Complete the following addition table:

+ | -3 | -4 | -2 | +1 | +2 | +3 |

-2 | ||||||

-3 | ||||||

0 | ||||||

+1 | ||||||

+2 |

Solution:

+ | -3 | -4 | -2 | + 1 | +2 | +3 |

-2 | -5 | -6 | -4 | -1 | 0 | + 1 |

-3 | -6 | -7 | -5 | -2 | -1 | 0 |

0 | -3 | -4 | -2 | + 1 | +2 | +3 |

+ 1 | -2 | -3 | -1 | +2 | +3 | +4 |

+2 | -1 | -2 | 0 | +3 | +4 | +5 |